Penolakan UU Cipta Kerja 2020 (Analisis Schoemacher & Reese Pemberitaan Cnnindonesia.Com) - Ari Cahyo Nugroho; Syarifuddin Syarifuddin (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
The Omnibus Law first appeared in President Jokowi's speech during his inauguration on October 20, 2019. The omnibus law is a concept to form the main law to regulate issues previously regulated by a number of laws or one law that simultaneously revises several laws. This law is intended to streamline regulations in terms of numbers so that they are more targeted. Of course, the media are closely related to this news. The media are considered able to mediate this polemic. The media, in this situation, is needed to bring diverse ideas, especially people’s aspiration. This linkage is described in the Hierarchy of Influence Theory of Pamela J Shoemaker and Stephen D. Reese (Pamela J Shoemaker and Stephen D. Reese 1996). This theory explains the effect on the content of media coverage by internal and external influences. In connection with this writing, the existence of cyber media in Indonesia is also part of freedom of opinion, freedom of expression, and freedom of the press. One of them is the cyber media news site CNNIndonesia.com. The CNNIndonesia.com news site is owned by Trans Media. CNNIndonesia.com provides local and international content, with a focus on general news, business, sports, technology, and entertainment. CNNIndonesia.com was launched on 20 October 2014 with Yusuf Arifin as editor-in-chief. This paper focuses on the relationship between Pamela J Shoemaker and Stephen D. Reese's Hierarchical Influence Theory with the reporting of Omnibus Law on CNNIndonesia.com. The results of the analysis show that CNNIndonesia.com media has very little reporting on how the Omnibus Law endangers press freedom and journalistic work itself. This further confirms that online media (CNNIndonesia.com) does not have an agenda. Keyword: News, Schomacher and Reese Analysis